The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1038/sj.jes.7500526
|View full text |Cite
|
Sign up to set email alerts
|

Di-n-butylphthalate and butylbenzylphthalate — urinary metabolite levels and estimated daily intakes: pilot study for the German Environmental Survey on children

Abstract: We analysed urine samples from the 2001/2002 pilot study of the German Environmental Survey on Children (GerES IV) for the concentrations of the di-n-butylphthalate (DnBP) metabolite mono-n-butylphthalate (MnBP) and the butlybenzylphthalate (BBzP) metabolite mono-benzyl-phthalate (MBzP). The study population consisted of 239 children (106 boys, 133 girls) aged between 2 and 14 years (median 8.5 years). We applied two calculation models to estimate the daily intake for the two parent phthalates from metabolite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
75
1
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(87 citation statements)
references
References 46 publications
7
75
1
2
Order By: Relevance
“…These equations give results that are similar to a previously reported ecologic equation (Institute of Algorithmic Medicine, 2006, based on the data of Viteri and Alvarado (1970)) for both male and female daily CE (mg/day) ¼ (252/ Ht)À8.01 þ 0.0817 Ht, with height in cm, age from birth to 8.5 years. This similarity supports the use of creatinine correction as being more stable than a volume correction (estimated daily volume of urine to scale up a single void sample) that may lead to a higher estimate (Koch et al, 2006). …”
Section: Ce For Ages 3-18 Yearssupporting
confidence: 55%
See 1 more Smart Citation
“…These equations give results that are similar to a previously reported ecologic equation (Institute of Algorithmic Medicine, 2006, based on the data of Viteri and Alvarado (1970)) for both male and female daily CE (mg/day) ¼ (252/ Ht)À8.01 þ 0.0817 Ht, with height in cm, age from birth to 8.5 years. This similarity supports the use of creatinine correction as being more stable than a volume correction (estimated daily volume of urine to scale up a single void sample) that may lead to a higher estimate (Koch et al, 2006). …”
Section: Ce For Ages 3-18 Yearssupporting
confidence: 55%
“…Koch et al (2006) have also used these same CE data to estimate average daily intake of di-n-butylphthalate and butylbenzylphthalate in German children based on their urine analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Biomarker-based estimates of phthalate daily intake are available for adults and children in the United States, Germany, Korea, Japan, and Taiwan (David, 2000;Kohn et al, 2000;Koo et al, 2002;Clark et al, 2003;Itoh et al, 2005;Koo and Lee 2005;Itoh et al, 2007;Koch et al, 2007Koch et al, , 2006Koch et al, , 2003bWittassek et al, 2007;Chen et al, 2008;Wittassek and Angerer, 2008), for pregnant women (Marsee et al, 2006) and for infants in neonatal intensive care units (Calafat and McKee, 2006;Weuve et al, 2006); however, phthalate daily intake estimates for occupationally exposed groups are lacking. In 2003-2005, the National Institute for Occupational Safety and Health (NIOSH) conducted a preliminary study of phthalate exposures among 156 workers in eight industry sectors where materials containing diethyl phthalate (DEP), dibutyl phthalate (DBP), and di(2-ethylhexyl) phthalate (DEHP) were manufactured or used as part of the workers' regular job duties.…”
Section: Introductionmentioning
confidence: 99%
“…35) The daily DBP intake of university students were similar to children in median, but higher in 95th percentile. These finding indicated that children had the highest DEHP and DBP daily intakes, follow by university students.…”
Section: )mentioning
confidence: 85%